Perspectives on contemporary lesbian relationships. Issue 1 (2nd January 2017) - Holley, Sarah R.
ABSTRACT: This article introduces the special issue on contemporary lesbian relationships. The beginning notes some of the prominent changes that have occurred in the past 15 years in the visibility and positive representation of lesbian couples in our popular U.S. culture. The remainder focuses on identifying and summarizing the primary themes of the special issue, including the implications of changes in marriage rights, the acknowledgment and exploration of the effects of sexual minority stress, and a shift in the framing of research to better reflect the diversity of lesbian relationship experiences.